The Relationship between Digital Marketing and Entrepreneurship in the MYPES of Footwear Sector in APIAT Trade Fair in Trujillo, Peru - Pineda Castillo, Santos Alberto (2023)
The objective of this research was to determine the impact of digital marketing on the entrepreneurship of MYPES in the footwear sector of the APIAT trade fair of Trujillo 2022, the type of research was applied, with a quantitative research approach and a correlational research design. The sample consisted of 65 small and medium-sized entrepreneurs in the footwear sector of the Trujillo APIAT trade fair. The questionnaire for digital marketing and questionnaire for entrepreneurship were used for data collection. The information was processed in SPSS Ver 26 software. As a result, digital marketing has a high incidence on entrepreneurship. It was determined normative framework, referential framework, conceptual framework and the conceptual framework have a high incidence on entrepreneurship, that the conceptual framework has a high impact on entrepreneurship, theoretical framework and philosophical framework have a moderate impact on entrepreneurship.